CYBERACTIVISM ANAK-ANAK BROKEN HOME DI INSTAGRAM @BEHOME.ID - Hafidhatul Fathany (Linimasa : Jurnal Ilmu Komunikasi, 2025)
Digital media has made accessing information, news, experiences, and opinions a breeze for users. Thanks to advancements in technology, internet networks, and social media, this interaction can now be done with ease, right at the palm of your hand. In Indonesia, Instagram ranks second in terms of the highest number of social media users. Its various features make interaction easy and varied, forming new communities based on common interests, hobbies, and backgrounds. One such virtual community on Instagram is BeHome, which comprises children from broken homes. This research delves into the cyberactivism activities carried out by these children on the social media platform @behome.id. The study employs cyberactivism theory, adaptive strategy theory, and connective action theory while utilizing a qualitative methodology with a netnographic approach. The research data was collected through observation and in-depth interviews with BeHome representatives (BeHome Ambassadors) and active BeHome followers. The results of the study demonstrate that cyberactivism is a form of resistance to the stigma associated with broken home children. John W. Bennett's three adaptive strategies, namely adjusting actions to meet environmental expectations, utilizing human resources as an important factor, and easing each other's burdens, are employed. Solidarity in the community is voluntary and not binding, as per the concept of connective action theory.